Engineering sub-10 nm fluorescent nanodiamonds for quantum enhanced biosensing - Alkahtani, Masfer H.; Alzahrani, Yahya A.; Hemmer, Philip R. (Frontiers in Quantum Science and Technology, 2023)
There is an increasing interest in the sensing of magnetic, electric, and temperature effects in biological systems on the nanoscale. While there are existing classical sensors, the possibility of using quantum systems promises improved sensitivity and faster acquisition time. So far, much progress has been made in diamond color centers like the nitrogen-vacancy (NV) which not only satisfy key requirements for biosensing, like extraordinary photostability and non-toxicity, but they also show promise as room-temperature quantum computers/sensors. Unfortunately, the most-impressive demonstrations have been done in bulk diamond, since NVs in fluorescent nanodiamonds (FNDs) tend to have inferior properties. Yet FNDs are required for widespread nanoscale biosensing. In order for FND-based quantum sensors to approach the performance of bulk diamond, novel approaches are needed for their fabrication. To address this need we discuss opportunities for engineering the growth of FNDs.